Visual Informatics: Sustaining Research and Innovations Second International Visual Informatics Conference, IVIC 2011, Selangor, Malaysia, November 9-11, 2011, Proceedings, Part I - Badioze Zaman, Halimah; Robinson, Peter; Petrou, Maria; Olivier, Patrick; Shih, Timothy K.; Velastin, Sergio; Nyström, Ingela (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2011)
The two-volume set LNCS 7066 and LNCS 7067 constitutes the proceedings of the Second International Visual Informatics Conference, IVIC 2011, held in Selangor, Malaysia, during November 9-11, 2011. The 71 revised papers presented were carefully reviewed and selected for inclusion in these proceedings. They are organized in topical sections named computer vision and simulation; virtual image processing and engineering; visual computing; and visualisation and social computing. In addition the first volume contains two keynote speeches in full paper length, and one keynote abstract.